The Influence Of Phonological Awareness On Early Literacy Development - Deva Yanti Siregar; Khairani Khairani; Yani Lubis (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Phonological awareness, defined as the ability to recognize and manipulate the sounds of language, has been widely recognized as a critical factor in early literacy development. This article aims to explore the influence of phonological awareness on the acquisition of reading and writing skills during the early stages of education. The research examines the relationship between phonological awareness and various aspects of literacy, including decoding, spelling, and reading comprehension. Numerous studies have demonstrated a strong correlation between phonological awareness and early literacy outcomes. Children with well-developed phonological awareness skills exhibit better phonemic awareness, word recognition, and reading comprehension abilities. Conversely, deficits in phonological awareness often manifest as difficulties in decoding words, spelling, and overall reading proficiency. The article further investigates the instructional strategies and interventions that can enhance phonological awareness in young learners. Effective techniques, such as phonemic awareness exercises, explicit instruction, and multisensory approaches, are discussed. Additionally, the article highlights the significance of early identification and intervention for children at risk of phonological awareness difficulties. Understanding the impact of phonological awareness on early literacy development is crucial for educators, parents, and policymakers. By recognizing the importance of phonological awareness and implementing appropriate instructional practices, it is possible to foster strong foundations for reading and writing skills, ultimately supporting children's overall literacy achievement.